2018
DOI: 10.3389/fmicb.2018.01836
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity and Epidemiology of Human Rhinovirus Among Children With Severe Acute Respiratory Tract Infection in Shanghai, 2013–2015

Abstract: Human rhinovirus (HRV), and particularly HRV-C, is increasingly recognized as a cause of severe acute respiratory infections (SARIs). However, little is known about the genotypic diversity and epidemiology of HRV among children with SARI. Thus, we investigated the genotypic diversity and epidemiology of HRV in children with SARI in China over a 2-year period. In total 1,003, nasopharyngeal aspirates were collected from children hospitalized with SARI in Shanghai from 2013 to 2015. HRV was screened for by a PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 30 publications
14
36
1
Order By: Relevance
“…In Shanghai, China, HRV A (14.0%) was the predominant species, followed by HRV C (5.6%), then HRV B (2.1%) in SARIs, too. However, their results showed no significant difference in clinical symptoms according to HRV species (14). In the study, when gender, age and co-infection were all considered and using HRV C as the control species, HRV A was a dangerous factor to cause severe clinical outcome (OR=1.983>1 ,95% CI=1.091-3.605, the lower limit of 95% CI>1) (p=0.025), and HRV B has no relationship with severity of clinical outcome.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In Shanghai, China, HRV A (14.0%) was the predominant species, followed by HRV C (5.6%), then HRV B (2.1%) in SARIs, too. However, their results showed no significant difference in clinical symptoms according to HRV species (14). In the study, when gender, age and co-infection were all considered and using HRV C as the control species, HRV A was a dangerous factor to cause severe clinical outcome (OR=1.983>1 ,95% CI=1.091-3.605, the lower limit of 95% CI>1) (p=0.025), and HRV B has no relationship with severity of clinical outcome.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown in a number of studies that HRV A and HRV C were associated with more severe outcome in the pediatric population (7)(8)(9)(10)(11)(12). Other results supported that HRV C, which may be one of the key factors in the association of HRVs with asthma (13), may cause more severe illness, and is more frequently associated with wheezing episodes, asthma exacerbations, and lower respiratory tract infections than HRV A and HRV B (8,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 92%
“…The majority of studies conducted in many parts of the world have consistently reported that RV-A, B, and C are detected in 48% to 65%, 2% to 12%, and 26% to 44% of samples, respectively. 4,5,7,9,12,[14][15][16][17][18][19]26,27,30,[32][33][34][35] Our study is unique to many other studies in that we assessed viral types in a communitybased rural setting, using prospective surveillance, compared with the clinic or hospital-based surveillance in more urban settings.…”
Section: Illness Severitymentioning
confidence: 99%
“…37 No associations between RV species and illness severity have been reported by others. 4,[14][15][16]18,19,30,38 However, some studies have shown that RV-C species are more likely to cause LRT illnesses than RV-A 5,9 including specific clinical findings, such as wheezing, 12,39 asthma, 31 rhonchi, vomiting, 13 and viremia. 26 The discrepancies between these studies may be due to the patients that were tested.…”
Section: Illness Severitymentioning
confidence: 99%
See 1 more Smart Citation